2021
DOI: 10.3390/atmos12010097
|View full text |Cite
|
Sign up to set email alerts
|

Future Projections and Uncertainty Assessment of Precipitation Extremes in the Korean Peninsula from the CMIP6 Ensemble with a Statistical Framework

Abstract: Scientists occasionally predict projected changes in extreme climate using multi-model ensemble methods that combine predictions from individual simulation models. To predict future changes in precipitation extremes in the Korean peninsula, we examined the observed data and 21 models of the Coupled Model Inter-Comparison Project Phase 6 (CMIP6) over East Asia. We applied generalized extreme value distribution (GEVD) to a series of annual maximum daily precipitation (AMP1) data. Multivariate bias-corrected simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(105 reference statements)
1
6
0
Order By: Relevance
“…In applying the PI-weighting method, we follow ways of selecting two shape parameters [43], based on the p-value of the chi-square statistic and entropy. The methods are simple and intuitively appealing, although they may need more justification to use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In applying the PI-weighting method, we follow ways of selecting two shape parameters [43], based on the p-value of the chi-square statistic and entropy. The methods are simple and intuitively appealing, although they may need more justification to use.…”
Section: Discussionmentioning
confidence: 99%
“…This leave-one-out procedure needs a huge computing time. To overcome this computational burden, we follow a relatively simple method proposed by [43] to determine the shape parameters. More details in computing the distance S ij and in selecting the shape parameters are given in the Supplementary Material.…”
Section: Performance and Independence Weighting For Ensemblesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data have demonstrated that the intensity and frequency of extreme rainfall events have increased due to climate change. Furthermore, it is anticipated that the intensity and frequency of precipitation will continue to increase in the future (Li et al, 2021; Shin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed a 22.5% and 19.2% increase in runoff under the SSP2-4.5 and SSP5-8.5 scenarios, respectively. Shin et al (2021) predicted extreme PCP events on the Korean Peninsula. They Utilized 21 CMIP6 GCMs under three scenarios: SSP2-4.5, SSP3-7.0, and SSP5-8.5.…”
Section: Introductionmentioning
confidence: 99%